Implementation of the UN Genocide Convention of 1948 in the National Laws of the State Parties - ADIBAYEVA, Alina Kuanishbekovna (Journal of Advanced Research in Law and Economics; Vol 7 No 6 (2016): Vol 7, No 6(2016): JARLE, Volume VII, Issue 6(20), Fall 2016, 2017)
The article shows that genocide is one of the deadliest international crimes encroaching on the safety of existence of national, ethnical, racial, and religious groups of people. The author found out that criminal responsibility for commission of this crime is stipulated both in the international regulatory documents and in the national legislation. The author define genocide the same way as the branch of the international law does: any of the following acts committed with intent to destroy, in whole or in part, a national, ethnical, racial or religious group, as such: (a) killing members of the group; (b) causing serious bodily or mental harm to members of the group; (c) deliberately inflicting on the group conditions of life calculated to bring about its physical destruction in whole or in part; d) imposing measures intended to prevent births within the group; e) forcibly transferring children of the group to another group, which is captured in the Convention on the Prevention and Punishment of the Crime of Genocide adopted on 9 December 1948. Additionally, the document allocates the common duty to all the States that is to prevent and punish for commission of genocide and to use for this purpose the measures aimed at implementation of its provisions. The author show that based on the specified provisions in legislations of the majority of 147 States ratifying the Convention provides legal responsibility for commission of genocide.
Keywords: genocide, UN Convention, State Parties, implementation, national legislation